Can new quality productivity promote high-quality agricultural development?—An empirical study based on provincial panel data in China - Zhang, Simeng; Xie, Fengjie (Frontiers in Sustainable Food Systems, 2025)
The deep integration of new quality productivity (NQP) with the agricultural sector is an inevitable path to promoting high-quality agricultural development. This paper explores the role of NQP in enhancing the high-quality agricultural development using panel data from 30 provinces in China over the period 2012–2021. An evaluation index system was constructed to measure both NQP and the level of high-quality development of agriculture. Empirical analysis was conducted using fixed effect and threshold effect models to test the promotion effect of NQP on agricultural development. The results indicate that NQP significantly promotes high-quality agricultural development, a conclusion that remains robust after undergoing robustness tests. Heterogeneity analysis reveals regional differences, with the eastern region showing the strongest effect, followed by the central region, and the western region showing the weakest effect. Additionally, in areas with higher levels of marketization, the promoting effect of NQP is more pronounced. Further research shows a non-linear relationship between NQP and agricultural development, characterized by increasing marginal effects. The findings provide robust support for the practical application of NQP in agriculture to achieve high-quality development and offer significant theoretical foundations for policy-making.